An updated checklist of the vascular flora alien to Italy. (4th May 2018) - Galasso, G.; Conti, F.; Peruzzi, L.; Ardenghi, N. M. G.; Banfi, E.; Celesti-Grapow, L.; Albano, A.; Alessandrini, A.; Bacchetta, G.; Ballelli, S.; Bandini Mazzanti, M.; Barberis, G.; et al.
Abstract: An updated inventory of the vascular flora alien to Italy, providing details on the occurrence at regional level, is presented. The checklist includes 1597 species, subspecies, and hybrids, distributed in 725 genera and 152 families; 2 taxa are lycophytes, 11 ferns and fern allies, 33 gymnosperms, and 1551 angiosperms. 157 taxa are archaeophytes and 1440 neophytes. The alien taxa currently established in Italy are 791 (570 naturalized and 221 invasive), while 705 taxa are casual aliens, 4 are not assessed, 7 are of unknown regional distribution, 47 have not been confirmed in recent times, 3 are considered extinct or possibly extinct in the country, and 40 are doubtfully occurring in Italy. This checklist allows to establish an up-to-date number (9792) of taxa constituting the whole (native and alien) Italian flora.